Prophylactic Fixation Can Be Cost-effective in Preventing a Contralateral Bisphosphonate-associated Femur Fracture. Issue 3 (March 2019) - Jiang, Sam Y.; Kaufman, David J.; Chien, Bonnie Y.; Longoria, Michael; Shachter, Ross; Bishop, Julius A.
Abstract: Background: Bisphosphonates reduce the risk of fractures associated with osteoporosis but increase the risk of atypical subtrochanteric femur fractures. After unilateral atypical femur fracture, there is risk of contralateral fracture, but the indications for prophylactic fixation are controversial. Questions/purposes: The purpose of this study is to use Markov modeling to determine whether contralateral prophylactic femur fracture fixation is cost-effective after a bisphosphonate-associated atypical femur fracture and, if so, what patient-related factors may influence that determination. Methods: Markov modeling was used to determine the cost-effectiveness of contralateral prophylactic fixation after an initial atypical femur fracture. Simulated patients aged 60 to 90 years were included and separated into standard and high fracture risk cohorts. Patients with standard fracture risk were defined as those presenting with one atypical femur fracture but without symptoms or findings in the contralateral femur, whereas patients with high fracture risk were typified as those with more than one risk factor, including Asian ethnicity, prodromal pain, femoral geometry changes, or radiographic findings in the contralateral femur. Outcome probabilities and utilities were derived from studies matching to patient characteristics, and fragility fracture literature was used when atypical femur fracture data were not available. Associated costs were largely derived from Medicare 2015 reimbursement rates. Sensitivity analysis was performed on all model parameters within defined ranges. Results: Prophylactic fixation for a 70-year-old patient with standard risk for fracture costs USD 131, 300/quality-adjusted life-year (QALY) and for high-risk patients costs USD 22, 400/QALY. Sensitivity analysis revealed that prophylaxis for high-risk patients is cost-effective at USD 100, 000/QALY when the cost of prophylaxis was less than USD 29, 400, the probability of prophylaxis complications was less than 21%, or if the patient was younger than 89 years old. The parameters to which the model was most sensitive were the cost of prophylaxis, patient age, and probability of prophylaxis-related complications. Conclusions: Prophylactic fixation of the contralateral side after unilateral atypical femur fracture is not cost-effective for standard-risk patients but is cost-effective among high-risk patients between 60 and 89 years of age with a high risk for an atypical femur fracture defined by patients with more than one risk factor such as Asian ethnicity, prodromal pain, varus proximal femur geometry, femoral bowing, or radiographic changes such as periosteal beaking and a transverse radiolucent line. However, our findings are based on several key assumptions for modeling such as the probability of fractures and complications, the costs associated for each health state, and the risks of surgical treatment. Future research should prospectively evaluate the degree of risk contributed by known radiographic and demographic parameters to guide management of the contralateral femur after a patient presents with an atypical femur fracture. Level of Evidence: Level III, economic and decision analyses.